DNA variation at the rp49 gene region in Drosophila madeirensis and D. subobscura from Madeira: inferences about the origin of an insular endemic species - Khadem, M. (2021)
An 1.6-kb fragment spanning the rp49 gene was sequenced in 16 lines of Drosophila subobscura from Madeira and in 22 lines of the endemic species D. madeirensis. Nucleotide diversity in D. subobscura from Madeira (p 0.0081) was similar to that in lines from Spain carrying the O3+4 chromosomal arrangement (p 0.0080). No signi®cant genetic differentiation was detected between insular and continental O3+4 lines of D. subobscura. These results are compatible both with a rather recent and massive colonization, and with multiple colonization events from the continent. Nucleotide diversity in D. madeirensis (p 0.0076) was similar to that in D. subobscura, which deviates from the expectation, under strict neutrality, of a lower level of variation in an insular species with a small population size. The observed numbers of shared polymorphisms and of ®xed differences between D. madeirensis and D. subobscura are compatible with the isolation model of speciation, where shared polymorphisms are due to common ancestry.